2012
DOI: 10.21101/cejph.a3735
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Influenza-Like Illness Through Medication Sales

Abstract: Monitoring sales of medications is a potential candidate for an early signal of a seasonal influenza epidemic. To test this theory, the data from a traditional, consultation-oriented influenza surveillance system were compared to medication sales and a predictive model was developed. Weekly influenza-like incidence rates from the National Influenza Sentinel Surveillance System were compared to sales of seven groups of medications (nasal decongestants, medicines for sore throat (MST), antitussives, mucolytics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…The use of sales information for adult and child remedy products has been suggested as a useful augmentation to traditional surveillance mechanisms,8 13 14 but has not been tested within the UK. Previous studies have suggested that localised retail sales data is more reflective of surveyed influenza patterns than national level data 11 12 28.…”
Section: Discussionmentioning
confidence: 99%
“…The use of sales information for adult and child remedy products has been suggested as a useful augmentation to traditional surveillance mechanisms,8 13 14 but has not been tested within the UK. Previous studies have suggested that localised retail sales data is more reflective of surveyed influenza patterns than national level data 11 12 28.…”
Section: Discussionmentioning
confidence: 99%
“…Medication sales [74][75][76][77][78][79] Over-the-counter drug sales correlated with infl uenza activity Self-reporting participatory systems [81][82][83] Online-based surveillance system relying on voluntary participation Informal surveillance and epidemic intelligence [85][86][87][88][89][90][91][92][93]94 Detect relevant information from the internet, nationally and internationally The Global Public Health Intelligence Network (GPHIN) is a Canadian initiative that draws on the capacity of the internet and worldwide news coverage of health events. 93 GPHIN creates an early warning of outbreaks by monitoring internet media, including news wires and websites, to detect and report disease outbreaks.…”
Section: Informal Surveillance and Epidemic Intelligencementioning
confidence: 99%
“…Following this, the potential of using several different syndromic data sources as a tool in local influenza surveillance was examined at the beginning of this thesis (in the eHealth study). The findings were promising and corresponded to the recent outcomes worldwide (Kim et al 2013, Timpka et al 2014a, Nagel et al 2013, Yom-Tov et al 2014, Kirian & Weintraub 2010, Socan et al 2012). However, it was concluded that further longitudinal research incorporating prospective evaluations of actionable alerts (Milinovich et al 2014) is required before eHealth surveillance systems can be used in routine public health practice.…”
Section: Data Data Sourcessupporting
confidence: 77%
“…In the past few years, a considerable amount of research has focused on the use of interactive health information technology-referred to as eHealth systems-to improve the effectiveness of infectious disease surveillance (Castillo-Salgado 2010). Researchers have focused on the use of Internet search engines (Kim et al 2013, Sharpe et al 2016, Pollett et al 2017, telenursing data (Timpka et al 2014a), mini-blogs (Nagel et al 2013, YomTov et al 2014, Sharpe et al 2016, and records of over-the-counter drug sales (Kirian & Weintraub 2010, Socan et al 2012. This implies that the area where the need for knowledge is most immediate is the detection and prediction of influenza activity at local levels (Shaman et al 2013).…”
Section: Introductionmentioning
confidence: 99%